Analysis of sensitivity of a compliant micro-gripper - Ho , Nhat Linh; Dao , Thanh Phong; Le, Hieu Giang (Journal of Technical Education Science, 2021)
This paper aims to analyze effects of design parameters on the sensitivity of compliant micro-gripper. The micro-gripper is constructed based on a four-bar mechanism and a concept of compliant mechanism with circular hinges. The three basic parameters to be considered such as the width of the circular hinge, the thickness of gripper and the material properties. The analysis process is done through ANSYS software and Matlab software. Firstly, the displacement is analyzed to determine the maximum displacement of jaws. Subsequently, the natural frequency characteristics of the gripper are considered. Finally, through the natural frequency characteristics, the effects of each parameter on the sensitivity are analyzed. The results showed that the design parameters of gripper and the sensitivity have a close relationship with each other. Therefore, they should be considered in the design process of the compliant micro-gripper.